Correlating the chemical and spectroscopic characteristics of natural organic matter with the photodegradation of sulfamerazine. (15th April 2016) - Batista, Ana Paula S.; Teixeira, Antonio Carlos S.C.; Cooper, William J.; Cottrell, Barbara A.
Abstract: The role of aquatic natural organic matter (NOM) in the removal of contaminants of emerging concern has been widely studied. Sulfamerazine (SMR), a sulfonamide antibiotic detected in aquatic environments, is implicated in environmental toxicity and may contribute to the resistance of bacteria to antibiotics. In aquatic systems sulfonamides may undergo direct photodegradation, and, indirect photodegradation through the generation of reactive species. Because some forms of NOM inhibit the photodegradation there is an increasing interest in correlating the spectroscopic parameters of NOM as potential indicators of its degradation in natural waters. Under the conditions used in this study, SMR hydrolysis was shown to be negligible; however, direct photolysis is a significant in most of the solutions studied. Photodegradation was investigated using standard solutions of NOM: Suwannee River natural organic matter (SRNOM), Suwannee River humic acid (SRHA), Suwannee River fulvic acid (SRFA), and Aldrich humic acid (AHA). The steady-state concentrations and formation rates of the reactive species and the SMR degradation rate constants ( k 1 ) were correlated with NOM spectroscopic parameters determined using UV–vis absorption, excitation-emission matrix (EEM) fluorescence spectroscopy, and proton nuclear magnetic resonance ( 1 H NMR). SMR degradation rate constants ( k 1 ) were correlated with steady-state concentrations of NOM triplet-excited state ([ 3 NOM ∗ ]ss ) and the corresponding formation rates ( 3 NOM*) for SRNOM, SRHA, and AHA. The efficiency of SMR degradation was highest in AHA solution and was inhibited in solutions of SRFA. The steady-state concentrations of singlet oxygen ([ 1 O2 ]ss ) and the SMR degradation rate constants with singlet oxygen ( k 1O2 ) were linearly correlated with the total fluorescence and inversely correlated with the carbohydrate/protein content ( 1 H NMR) for all forms of NOM. The total fluorescence and EEMs Peak A were confirmed as indicators of 1 O2 formation. Specific ultraviolet absorbance at 254 nm (SUVA254 ) and aromaticity showed potential correlations with the steady-state concentrations of hydroxyl radical ([HO]ss ) and the corresponding formation rates (HO). Graphical abstract: Highlights: Direct and indirect degradation of sulfamerazine under simulated sunlight. Formation rate and steady state concentration of reactive species. Correlation of spectroscopic properties of NOM and reactivity were assessed. NOM reactivity toward sulfamerazine degradation was discussed.